Relationship between hypertension and periapical lesion: an in vitro and in vivo study - Martins, Christine Men; Sasaki, Hajime; Hirai, Kimito; Andrada, Ana Cristina; Gomes Filho, João Eduardo [UNESP] (FapUNIFESP (SciELO), 2016)
The aim of this study was to compare potential aspects of periapical lesion formation in hypertensive and normotensive conditions using hypertensive (BPH/2J) and wild-type control (BPN/3J) mice. The mandibular first molars of both strains had their dental pulp exposed. At day 21 the mice were euthanized and right mandibular molars were used to evaluate the size and phenotype of apical periodontitis by microCT. Proteins were extracted from periapical lesion on the left side and the expressions of IL1α, IL1β and TNFα were analyzed by ELISA. Bone marrow stem cells were isolated from adult mice femurs from 2 strains and osteoclast differentiation was evaluated by tartrate-resistant acid phosphatase (TRAP) in vitro. The amount of differentiated osteoclastic cells was nearly double in hypertensive mice when compared to the normotensive strain (p < 0.03). Periapical lesion size did not differ between hypertensive and normotensive strains (p > 0.7). IL1α, IL1β and TNFα cytokines expressions were similar for both systemic conditions (p > 0.05). Despite the fact that no differences could be observed in periapical lesion size and cytokines expressions on the systemic conditions tested, hypertension showed an elevated number of osteoclast differentiation.